2008
DOI: 10.1242/jcs.020958
|View full text |Cite
|
Sign up to set email alerts
|

Integrin clustering enables anandamide-induced Ca2+ signaling in endothelial cells via GPR55 by protection against CB1-receptor-triggered repression

Abstract: Summary Although the endocannabinoid anandamide is frequently described to act predominantly in the cardiovascular system, the molecular mechanisms of its signaling remained unclear. In human endothelial cells, two receptors for anandamide were found, which were characterized as cannabinoid 1 receptor (CB1R; CNR1) and G-protein-coupled receptor 55 (GPR55). Both receptors trigger distinct signaling pathways. It crucially depends on the activation status of integrins which signaling cascade becomes promoted upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
180
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(194 citation statements)
references
References 97 publications
7
180
3
Order By: Relevance
“…Previous studies have highlighted the involvement of the cannabinoid receptors CB 1 and CB 2 in the local and/or central control of bone mass (2,3,33). Opinion is divided as to whether endocannabinoids have the ability to act as agonists of GPR55 (6,11,12,19,26), but our findings introduce the possibility that the effect of certain endocannabinoids on bone cells may be mediated, at least in part, via GPR55. Lysophospholipids play a role in many physiological and pathophysiological processes and now are recognized as extracellular signaling molecules as well as precursors of phospholipid synthesis (34).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Previous studies have highlighted the involvement of the cannabinoid receptors CB 1 and CB 2 in the local and/or central control of bone mass (2,3,33). Opinion is divided as to whether endocannabinoids have the ability to act as agonists of GPR55 (6,11,12,19,26), but our findings introduce the possibility that the effect of certain endocannabinoids on bone cells may be mediated, at least in part, via GPR55. Lysophospholipids play a role in many physiological and pathophysiological processes and now are recognized as extracellular signaling molecules as well as precursors of phospholipid synthesis (34).…”
Section: Discussionmentioning
confidence: 70%
“…LPI (and, to a lesser extent, O-1602) also caused activation of ERK in osteoclasts; ERK is associated with increased osteoclast activity and survival (23)(24)(25). Although some studies have failed to show that ERK lies downstream of GPR55 (19), other studies have demonstrated robust GPR55-mediated ERK activation (11,26). The contradictory nature of these findings may relate to the concept of functional selectivity (27,28), whereby different signaling pathways (e.g., Rho and ERK) are activated in an agonist-and tissue-specific manner (8).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in mice lacking GPR55 have reported a reduction in inflammatory and neuropathic pain (1), and these mice have increased bone mass (2). Subsequently, studies have established that the endogenous lysophospholipid LPI 2 activates GPR55 (3)(4)(5)(6)(7)(8)(9)(10). In certain cancer cell lines, GPR55 is highly expressed, and LPI mediates increased cell migration, invasion, and proliferation (3,8,11).…”
mentioning
confidence: 99%
“…They observed that integrin clusterings in the periphery of the cell occur within minutes, starts about after 3 minutes. There are also many recent studies on integrin clustering, such as by [19,48,39,52,55,2,25,45].…”
Section: Structural Components Of Cell-matrix Adhesionmentioning
confidence: 99%